A mixed methods analysis of U.S. perinatal providers’ attitudes towards culturally relevant infant mental health integration in obstetrical care - Kannikeswaran, Akshaya P.; Johnson, Angela Marie; Issa, Meriam; Muzik, Maria (Frontiers in Psychiatry, 2025)
IntroductionMany women in the perinatal period present to their women’s health providers with mental health concerns, which may impact the well-being of both the mother and baby. In this study, behavioral health consultants (BHCs) specially trained in the Infant Mental Health (IMH) approach, hereafter referred to as IMH-BHCs, were integrated into prenatal clinics whose patient populations include a significant proportion of Black, Indigenous, and People of Color (BIPOC) women. BIPOC women experience unique challenges in receiving culturally responsive perinatal and general healthcare. The aim of this study was to elucidate healthcare providers’ perceptions of IMH-BHC clinic integration on patient and provider outcomes, assess barriers to integrating behavioral health care into obstetric care environments, and understand the impact on quality of care delivery resulting from adding behavioral health support to perinatal populations.MethodsThis was a mixed-methods study conducted in Midwestern United States (Michigan); we collected survey responses from healthcare providers (n=52) on model knowledge and satisfaction; we also conducted a qualitative analysis of in-depth interviews with a subset (n=9). One-on-one interviews were guided by an ethnographic approach and focused on gathering thoughts, attitudes, and perceptions of health providers on integrating IMH-BHCs into their practice. Analysis included individual review, open coding, and thematic analysis of transcribed interviews using a grounded theory approach.ResultsQuantitative survey results reflected high knowledge about and engagement with the model. Survey respondents also endorsed the presence of the IMH-BHC improving scope focus and time management. Two main themes emerged with five sub-themes from our qualitative interviews. The main themes were: 1) initiation and engagement with the IMH-BHC model, and 2) evaluated effectiveness of the IMH-BHC. The sub-themes were: 1) IMH-BHC strategies to engage patients, 2) barriers to care facilitation, 3) continuity of care with IMH-BHC, 4) presence of the IMH-BHC may help aid in timely care, and 5) potential for reduction in provider workload and stress.ConclusionsOverall, the integration of IMH-BHCs into clinical settings was regarded as beneficial due to decreasing provider workload, increasing accessibility to mental health services for socially marginalized populations, and enhancing patient engagement. Further research is needed to mitigate barriers to IMH-BHC integration.